A Violence Against Women and Girls During Sars-CoV-2 Lockdown from Education Perspective - Francis Olawale Abulude; Ifeoluwa Ayodeji Abulude; Oluwadare Ayodele Oguntuyi; Arinola Oluwatoyin Gbotoso; Susan Omolade Ademilua (Universitas Pendidikan Indonesia (UPI), 2022)
This paper aims to discuss rape, one of the problems the pandemic caused in Nigeria from an educational perspective. To do justice to this, the internet, newspaper, personal communications, and journals were reviewed. From the sources, it was observed that: (i) within five months in Nigeria, over seven hundred cases were recorded (official); (ii) the forum of state governors declared a state of emergency on rape, (iii) NGOs and other stakeholders staged serial protests, (iv) the rape victims ranged between three years and 80 years old, (v) many deaths were reported during rapes, (vi) series of the cases were between fathers and their biological daughters, (vii) many ‘celebrities’ were involved, and so many others. Since this ugly incidence is becoming rampant, many ‘jungle justices are recommended to the government by the stakeholders, which include, castration of the male offenders, live imprisonment, wide publicity of the offenders through national dailies, and death penalties, just to mention a few. This paper recommends that to achieve the goal 5 targets of the SDGs or to eradicate or reduce the incidence of rape in Nigeria, all the stakeholders (men and women, parents, government, NGO, religious leaders, and others) should be ready to sacrifice all at their disposals to fight this menace called rape.